Alleviation of Synovial Inflammation of Juanbi-Tang on Collagen-Induced Arthritis and TNF-Tg Mice Model - Wang, Tengteng; Jia, Qingyun; Chen, Tao; Yin, Hao; Tian, Xiaoting; Lin, Xi; Liu, Yang; Zhao, Yongjian; Wang, Yongjun; Shi, Qi; Huang, Chenggang; Xu, Hao; et al. (Frontiers in Pharmacology, 2020)
Rheumatoid arthritis (RA) is a chronic autoimmune disease that primarily characterized by synovial inflammation. In this study, it was found that a traditional Chinese decoction–JuanBi Tang (JBT) could significantly attenuate the severity of arthritis both in collagen-induced arthritis (CIA) mice and in tumor necrosis factor transgenic (TNF-Tg) mice. According to histopathology stain and micro-CT score of ankle sections, JBT could significantly decrease inflammation area and reduce bone destruction of ankle joint in CIA mice. We also demonstrated that JBT could also alleviate ankle synovitis, restore bone area and cartilage area in TNF-tg mice. Decreased tartaric acid phosphatase positive(TRAP+) osteoclasts were observed in JBT group compared with saline group in the meanwhile. The pharmacological properties of this classical compound and the mechanisms underlying its therapeutic efficacy in the treatment of RA were investigated. Based on a network pharmacology, the computational prediction simulation of potential targets of JBT was executed, which indicated NF-kappa B pathway as the target. These results were validated in vitro. JBT suppressed the production of pro-inflammatory cytokines including TNF-α, interleukin-6(IL-6) and IL-8, and inhibited the expression of matrix metalloproteinases 1(MMP-1) in fibroblast-like synoviocytes(FLSs), derived from RA patients (MH7A cells). Furthermore, JBT could also suppress the phosphorylation of p38, JNK and p65 in TNF-α-treated MH7A cells. In summary, this study proved that JBT could inhibit synovial inflammation and bone destruction probably by blocking the phosphorylation of NF-kappa B pathway mediated production of proinﬂammatory effectors.